2023
DOI: 10.3390/en16073145
|View full text |Cite
|
Sign up to set email alerts
|

Co-Pyrolysis of Woody Biomass and Oil Shale in a Batch Reactor in CO2, CO2-H2O, and Ar Atmospheres

Abstract: The partial replacement of fossil fuels with biomass provides an alternative to producing cleaner and more sustainable energy and fuels. Conventional shale oil production infrastructure can potentially be used in co-pyrolysis with biomass to reduce the use of oil shale and decrease its environmental impact. The effect of adding 10 and 30 wt% woody biomasses (spruce, alder, pine, and birch) into oil shale was studied through intermediate co-pyrolysis. The experiments were carried out in a batch reactor at 520 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…For example, this experimental instrument cannot quantitatively describe the fracture propagation process, so we can take a lesson from other research and take more factors into consideration, such as obtaining propagation length, opening width, and growing speed through high-speed imaging devices and image analysis software, and analyzing the influence of pore structure and natural fractures on fracture propagation [41,42], and the corresponding mathematical model needs to be established to describe and calculate it [43][44][45]. This would improve the quantitative analysis of the combined effects of fracturing fluid retention on fracture propagation and formation damage [46].…”
Section: Discussionmentioning
confidence: 99%
“…For example, this experimental instrument cannot quantitatively describe the fracture propagation process, so we can take a lesson from other research and take more factors into consideration, such as obtaining propagation length, opening width, and growing speed through high-speed imaging devices and image analysis software, and analyzing the influence of pore structure and natural fractures on fracture propagation [41,42], and the corresponding mathematical model needs to be established to describe and calculate it [43][44][45]. This would improve the quantitative analysis of the combined effects of fracturing fluid retention on fracture propagation and formation damage [46].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the N 2 injection, the increased pyrolysis weight loss rate of oil shale injected with CO 2 and H 2 O indicated that these compounds were involved in the reaction of organic matter, promoted its cleavage and released the volatile fraction from oil shale [16][17][18]. Figure 1…”
Section: Pyrolysis Behavior Of Oil Shalementioning
confidence: 99%